2016
DOI: 10.1002/ajmg.a.37650
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of rivastigmine in children with Down syndrome: A double blind placebo controlled trial

Abstract: Individuals with Down syndrome (DS) have decreased cholinergic function and an uneven profile of cognitive abilities, with more pronounced deficits in learning, memory, and expressive language. Cholinesterase inhibitors may improve cognitive function in adults and adolescents with DS, but studies in children with DS have been limited. This study aimed to: (i) investigate the safety and efficacy of rivastigmine treatment; (ii) build upon our open-label studies in children with DS in a double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Subtests from several editions of the Clinical Evaluation of Language Fundamentals (CELF) assessment have been more sensitive to change in trials than other standardized language measures reported, such as the Test of Problem Solving (TOPS) (Zachman, Jorgensen, Huisingh, & Barrett, ), Differential Abilities Scale‐II (DAS‐II) (Elliott, ), Peabody Picture Vocabulary Test‐Third Edition (PPVT‐III) (Dunn & Dunn, ), and the Test of Reception of Grammar, Version 2 (TROG‐II) (Bishop, ) with some notable caveats. The Clinical Evaluation of Language Fundamentals‐Preschool (CELP‐P) Expressive Language Score and Total Language Score (Wiig, Secord, & Semel, ) detected treatment effects among adolescents in an open trial (Heller, Spiridigliozzi, Crissman, Sullivan, et al, ), with some evidence of ceiling effects, but was not sensitive to performance changes in a longer‐term follow‐up study (Heller et al, ), or when treatment group improvements were compared to placebo or comparison group changes (Kishnani et al, ; Spiridigliozzi et al, ). The Clinical Evaluation of Language Fundamentals‐Third Edition (CELF‐3) (Semel, Wiig, & Secord, ) Receptive and Expressive Language Scores and Total Score demonstrated utility in detecting treatment effects in an open‐label trial among children (Heller et al, ), but not in a large randomized controlled trial (RTC) with adults (Kishnani et al, ), which found a substantial number of participants at the floor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subtests from several editions of the Clinical Evaluation of Language Fundamentals (CELF) assessment have been more sensitive to change in trials than other standardized language measures reported, such as the Test of Problem Solving (TOPS) (Zachman, Jorgensen, Huisingh, & Barrett, ), Differential Abilities Scale‐II (DAS‐II) (Elliott, ), Peabody Picture Vocabulary Test‐Third Edition (PPVT‐III) (Dunn & Dunn, ), and the Test of Reception of Grammar, Version 2 (TROG‐II) (Bishop, ) with some notable caveats. The Clinical Evaluation of Language Fundamentals‐Preschool (CELP‐P) Expressive Language Score and Total Language Score (Wiig, Secord, & Semel, ) detected treatment effects among adolescents in an open trial (Heller, Spiridigliozzi, Crissman, Sullivan, et al, ), with some evidence of ceiling effects, but was not sensitive to performance changes in a longer‐term follow‐up study (Heller et al, ), or when treatment group improvements were compared to placebo or comparison group changes (Kishnani et al, ; Spiridigliozzi et al, ). The Clinical Evaluation of Language Fundamentals‐Third Edition (CELF‐3) (Semel, Wiig, & Secord, ) Receptive and Expressive Language Scores and Total Score demonstrated utility in detecting treatment effects in an open‐label trial among children (Heller et al, ), but not in a large randomized controlled trial (RTC) with adults (Kishnani et al, ), which found a substantial number of participants at the floor.…”
Section: Resultsmentioning
confidence: 99%
“…The CELF‐Revised (CELF‐R) (Semel, Wiig, & Secord, ) was not useful in detecting changes in an open‐label trial in adults (Heller et al, ). One noteworthy non‐standardized measure, the Test of Verbal Expression and Reasoning (TOVER) (Heller, Spiridigliozzi, & Kishnani, ), was used in four trials to assess expressive language (Heller, Spiridigliozzi, Crissman, Sullivan, et al, ; Heller et al, ; Kishnani et al, ; Spiridigliozzi et al, ). Although it only detected treatment effects in one open‐label trial among adolescents (Heller, Spiridigliozzi, Crissman, Sullivan, et al, ), it is mentioned here as a potentially useful non‐standardized measure for future development and research in DS and other neurodevelopmental disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivastigmine, a cholinergic agent used for the treatment of mild to moderate dementia, has also been studied in subjects with DSAD. In one double‐blind placebo‐controlled trial in 22 children and adolescents with DS, rivastigmine treatment did not improve cognition, language, or overall function . It was noted that subjects with DSAD tolerated rivastigmine therapy well.…”
Section: Alterations In Drug Disposition and Drug Responsementioning
confidence: 99%
“…In one double-blind placebo-controlled trial in 22 children and adolescents with DS, rivastigmine treatment did not improve cognition, language, or overall function. 26 It was noted that subjects with DSAD tolerated rivastigmine therapy well.…”
Section: Dementia and Psychiatric Disordersmentioning
confidence: 99%